O efeito China nas exportaç\~oes Brasileiras em terceiros mercados: Uma análise do constant market share - Lia Valls Pereira (Instituto de Pesquisa Econômica Aplicada (IPEA), 2014)
– Recent studies have called attention that China may limit the export diversification and technological upgrading of countries such as Brazil, in its traditional markets for manufactures. The aim of the research is to estimate the displacement of Brazilian exports by China in the markets of South American countries, Mexico, the United States, European Union and African countries (Nigeria, South Africa and Mozambique) between 2002-2011. The model of constant market share (CMS) was used to estimate the loss of Brazil and China coincident exports in the markets selected. The study shows that the losses attributed to China were higher in the United States in the years 2002-2006 and in South America increased thereafter. Moreover, in the South American region the biggest losses are in Chile, Colombia, Ecuador, Peru and Venezuela, but have been increasing in the markets of the other partners, especially in Argentina. Geographical proximity and the granting of a system of free intra - regional trade to a wide range of products did not prevent the displacement effect by China in the South American region Thus, Brazil's response should be in the direction of identifying and strengthening its competitive bases in the region through favorable policies to the creation of productive complementary - regional value chains.
Keywords: F10; F13; 330; China; international trade; Export; Brazil